تمثيل كارتوغ ا رفي لمستويات وتأثي ا رت التموث بغاز أحادي أوكسيد الكربون في مدينة البصرة، جنوبي الع ا رق ) - Karmalla, Hassen A. (University of Thi-Qar Journal of Science, 2019)
This study aims at the cartographic representation for the concentrations of carbon monoxide (CO) measured in ambient air of Basra City, by using a calibrated portable QREA II gas monitor. Measurements have been carried out for three days during Mar/2012, in 34 sampling stations which have been selected on an equal-distance grid of the study area map. A cartographic representation of the recorded values for this pollutant has been applied, in the way of isoclines, and an accurate identification could been obtained for spatial variability of the levels and impacts of carbon monoxide pollutant, and the affected areas have been exactly calculated, as well as actual number of affected population has been estimated. The present study concluded that about three quarter of the surveyed areas and habitants may be suffered from the studied pollutant, and that this problem perhaps worsens in accompanying with the anticipated rise in gaseous emissions released into the urban environment of the study area.